Metode Dakwah Suluak dan Tawajuah dalam Tarekat Naqsabandiyah - Fajri Ahmad (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2022)
Suluk is a series of congregational activities related to religious spirituality. Suluk is also interpreted as a way to get closer to God. While tawajjuh is the implementation of mysticism activities. Tawajuh is also interpreted as a meeting between a student and his sheikh face to face while teaching some dhikr. This study aims to determine the method of da'wah through suluk and tawajuah in the Naqsabandiyah Order, especially in Agam Regency, West Sumatra. The research method uses a qualitative method with purposave sampling technique, the researcher selects informants in the research who can provide information about the problem and the central phenomenon of the research. The da'wah method in the Naqsabandiyah tareqat is by means of suluak which is carried out every month of Ramadan for 40 days filled with certain practices to get closer to Allah. The month of Ramadan was chosen as a suluak activity because the month of Ramadan is a special month and has the virtue of worship being done. While the tawajuah is performed every Thursday once a week before noon until asr filled with congregational prayers followed by tawajuah, remembrance, study material from the murshid in the development of the Naqsabandiyah tareqat da'wah method using the suluak and tawajjuah methods which have implications for increasing the spirituality of the suluak congregation.